Land defragmentation in China: Does rental transaction inside acquaintance networks matter? - Tongwei Qiu; Xianlei Ma; Biliang Luo; S. T. Boris Choy; Qinying He (Journal of Applied Economics, 2022)
Using household-level data collected from three provinces in China, this paper investigates the links between land rentals conducted by acquaintances and land fragmentation. The econometric results indicate that the land rentals between acquaintances and those between non-acquaintances have similar effects on defragmentation when considering the endogeneity problem. Moreover, the land rentals between acquaintances have an increasingly positive impact on defragmentation as land rents increase. Further evidence shows that there is no significant difference in land rents between rental transactions conducted by acquaintances and those conducted by non-acquaintances, implying increasing marketization of land rentals inside acquaintance networks. Our findings validate the belief that the land rentals between acquaintances in China today have enormous potential for defragmentation.
Keywords: 330; China; acquaintances; Land fragmentation; land rentals; land rents